Understanding Truancy among Senior High School Students in the Offinso Municipality of Ghana - Andrew Kwame Yankyerah; Kwame Bediako Asare; Kennedy Nyeseh Ofori (Archives of Current Research International, 2023)
The aim of this descriptive survey was to identify the factors influencing truancy among Senior High school students in the Offinso Municipality of Ghana. There were 429 data-producing respondents comprising heads of institutions, teachers, students and parents who responded to the questionnaire. From the responses, we found that the sources of truancy among the students included the teachers, parents, school environment and the students themselves. The study results show that peer influence is the most common factor causing senior high school students in the municipality to be truants. Based on the study findings, we recommend, among others, intensified supervision of both students and teachers as well as strengthening Guidance and Counselling services among high schools in the Municipality and elsewhere.